PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) DENGAN PEMBELAHAN UMBI BIBIT PADA BEBERAPA JARAK TANAM - Wenny Deviana; Meiriani Meiriani; Sanggam Silitonga (Jurnal Agroekoteknologi, 2014)
Generally, propagation of shallot used bulbs as planting material. Cutting bulbs is one way todecrease the use of planting material. Cutting bulbs cause decreasing of growth point per plant. Bymore small plant spacing can balance growth point decreased, so that it can reach optimalproduction. This research was conducted at Jl. Pasar I No. 89 Tanjung Sari, Medan in Mei-August2013, using factorial randomized block design with two factor, i.e; cutting bulbs (no cutting bulbs,cutting 2 section, cutting 4 section) and plant spacing (10x15, 15x15 and 20x15 cm). Parameterobserved were plant height, number of leaves per plant, number of tillers per plant and dry bulbweight per plot. The result of the research showed that no cutting bulbs significantly increased onplant height, number of leaves per plant, number of tillers per plant and dry bulb weight per plotwhich is higher than the other treatments. 10x15 cm plant spacing significantly increased on drybulb weight per plot which is higher than the other treatments. Interaction between two factor notsignificantly effected on all parameter observed.Key words: cutting bulbs, plant spacing, shallot